2020
DOI: 10.1007/s10072-020-04743-5
|View full text |Cite
|
Sign up to set email alerts
|

Is DAT imaging abnormality in normal pressure hydrocephalus always suggestive of degeneration?

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a debated entity with controversial pathogenesis, diagnostic criteria, and predictors of response after ventriculoperitoneal shunt (VPS). Parkinsonian signs are frequently reported in the clinical picture, sometimes due to the coexistence of an underlying neurodegenerative parkinsonism and sometimes in the absence thereof. To distinguish these two scenarios is crucial, since they may carry different long-term response to CSF drainage. 123 I-FP-CIT-SPECT was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The results suggest that down-regulation of the postsynaptic D2 receptor could be related to a dysfunction of the cortico-striatal network due to hydrocephalus. This hypothesis on the mechanical effect exerted on the striatum by ventriculomegaly, which should be prominent in the caudate nucleus leading to the downregulation of dopaminergic transporters, has also been supported by single-photon emission computerized tomography (SPECT) studies [ 29 , 36 , 37 ]. In a recent paper striatal dopamine reuptake transporter density has been shown to differentiate iNPH patients with prevalent imbalance from those with major locomotor impairment, which also demonstrated a significant association between parkinsonism and striatal uptake only for the latter phenotype [ 38 ].…”
Section: Neuroimaging Support Of Parkinsonism In Inphmentioning
confidence: 88%
“…The results suggest that down-regulation of the postsynaptic D2 receptor could be related to a dysfunction of the cortico-striatal network due to hydrocephalus. This hypothesis on the mechanical effect exerted on the striatum by ventriculomegaly, which should be prominent in the caudate nucleus leading to the downregulation of dopaminergic transporters, has also been supported by single-photon emission computerized tomography (SPECT) studies [ 29 , 36 , 37 ]. In a recent paper striatal dopamine reuptake transporter density has been shown to differentiate iNPH patients with prevalent imbalance from those with major locomotor impairment, which also demonstrated a significant association between parkinsonism and striatal uptake only for the latter phenotype [ 38 ].…”
Section: Neuroimaging Support Of Parkinsonism In Inphmentioning
confidence: 88%
“…Surprisingly, some studies showed even a greater involvement in upper than lower extremities [14,19], and other authors described NPH patients with only upper limb parkinsonism [15,30]. The occurrence of bradykinesia and rigidity was not reported in the same body district by most of these studies [15,19,30]. As for rest tremor, it was seen mostly in the upper limbs [19,43,44], and only one patient had both upper and lower limb tremor [15].…”
Section: Other Cardinal Signs Of Parkinsonismmentioning
confidence: 92%
“…Parkinsonism can be present from the early stages of NPH and may progress with time [28]. A previous study described parkinsonism in 55 NPH patients with a mean disease duration of only 8.8 months [29], and found lower scores of the motor section (part III) of the Unified Parkinson's Disease Rating Scale (UPDRS) compared to other studies enrolling NPH patients with longer mean disease durations (from 2.2 to 3.1 years) [17,19,30]. Many studies applied scales developed for PD, especially when comparing the clinical features among subjects with NPH or other parkinsonian disorders or when assessing changes after intervention [14,17,20].…”
Section: Prevalence Of Parkinsonism In Normal Pressure Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these overlapping features, it is not uncommon for individuals with idiopathic PD or secondary parkinsonism to be suspected of having concomitant iNPH. DAT imaging is believed to be helpful for this purpose, but as a possible explanation, the mechanical effect exerted on the striatum by ventriculomegaly ultimately downregulates dopaminergic transporters, which may improve after shunt ( 72 ). Comorbidity with atypical parkinsonian disorders ( 73 , 74 ), MSA, PSP, CBD, or LBD affects the long-term prognosis of shunting in wide-based gait with staggering walk, lateral instability executive dysfunction ( 59 ), and apathy within 3 years of the treatment.…”
Section: Treatment Prognosis Due To Comorbid Neurodegenerative Diseasementioning
confidence: 99%